(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
A good regulatory quality reflects perceptions of the capability of the regulatory to frame and implement sound policies and regulations that permit and help all sector development. Following the spread of COVID-19 and increased financial volatility, the growth of FDI and trade outlook for the region in 2020 has been sharply downgraded. This study aims to observe empirically the effect of government spending in health sectors on economic growth during the early stage of the Covid-19 outbreak in Malaysia. As the world has awakened to the potential risks of Covid-19, there has been a massive effort to add capacity to the healthcare system rapidly. In Malaysia, apart from stressing the need for the public to strictly adhere to the Movement Control Order (MCO), the government provided an immediate boost in funding for healthcare services through the initial stage fiscal policy response to the Covid-19 outbreak. This research used dynamic panel data, also known as a longitudinal study, and observed data over the four months from December 2019 to March 2020 in 5 selected Asian countries that were involved with Covid-19. In terms of limitation, this study just focuses on four months of data from selected Asian countries involved with Covid-19. Panel causality results suggest bidirectional linkages between healthcare sector growth and government spending. Empirical findings suggest that fiscal policy reforms are required to channelize healthcare sector growth to more government spending resulting from fiscal policy designed by the government of Malaysia. In addition, panel causality results suggest bidirectional linkages between inward FDI and regulatory quality. Empirical findings suggest that economic policy reforms are required to channelize regulatory quality of COVID-19 to more foreign capital inflows. The governments of Asian countries should pull out policies on FDI inflows and the environment in order to achieve sustainable economic growth and development. The regulators of other countries should pull out fiscal policies on government policy to achieve sustainable economic growth and health sector growth development.